Management of innovative projects based on artificial intelligence applications in a turbulent environment - Bushuyev, Sergiy; Bushuyeva, Natalia; Lobok, Yevgen; Murovansky, Hleb (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2025)
The subject of this study is the management of innovative projects based on artificial intelligence (AI) in a turbulent environment, which is a particularly relevant situation for Ukraine due to its unique combination of challenges and opportunities. The full-scale invasion of Russia, economic instability in Ukraine, the outflow of personnel, and limited resources create a complex BANI environment (Brittle, Anxious, Nonlinear, Incomprehensible), which complicates traditional management approaches. The purpose of the study is to create a conceptual and mathematical model of effective management of innovative projects in the conditions of AI development and a turbulent BANI environment. At the same time, Ukraine demonstrates significant potential in the field of AI application, ranking second in the number of AI companies in Central and Eastern Europe according to the Ministry of Digital Transformation. The objectives of the study are to develop models for managing innovative projects in the context of digital transformation, covering the state administration "Diya", defence, medicine and education. AI allows you to predict risks, optimise resources and accelerate adaptation to changes, which is key to increasing competitiveness and resilience in war and post-conflict recovery. The relevance is also enhanced by the need to develop an ethical and legal framework for the use of AI, support start-up’s and create a national language model (LLM) that meets Ukraine’s European integration aspirations. The product of the study is a conceptual and mathematical model for the management of innovative projects and products based on AI in a turbulent environment. A mathematical model is proposed that is aimed at practical application by Ukrainian companies to create innovative products and increase their competitiveness. This model includes basic principles such as customer orientation, values, flexibility, risk management, interdisciplinarity, experimentation, use of technology, sustainability and innovation culture. The research process covers several stages – studying global trends and specifics of the state of Ukraine, identifying key principles of effective innovation management, such as flexibility, risk management and technological integration. The results of the study include models that prove that AI increases the efficiency of innovation projects through automation, forecasting and optimisation of resources based on a value system. War conditions emphasise the importance of AI for battlefield analysis and logistics. Conclusions – the study confirms that AI-based innovation project management in the turbulent environment of Ukraine is not only relevant, but also strategically important for recovery and development. The conceptual and mathematical model, as a product of the study, provides a theoretical and practical basis for creating valuable innovations, and the results emphasise the potential of AI to save resources, adapt to change and increase resilience. Further research can deepen these aspects, contributing to Ukraine’s innovative breakthrough.